Banten Historical Inheritances and Culture Tourism ( Culture and Inberitances as Glauce of Banten) - Asari Asari (Tsaqofah, 2002)
Culture Toirusm is a kind of travls done to widen one's perspective to study a tradition, a very of life, or an art and culture of society in developing tourism, the goverment of indonesia has made every effort to reach is goal by sending some artisits to performe indonesia art and culure, introducing traditional facilities that have indonesian traditional design since indonesia is very rich with unique and specific culture ( especially Banten Regent). By doing tihs indonesia can complete with other countries in asia and the pasific region in attracting tourist.